Electrochemical Platform for the Detection of Transmembrane Proteins Reconstituted into Liposomes - Vacek, Jan; Zatloukalova, Martina; Geleticova, Jaroslava; Kubala, Martin; Modriansky, Martin; Fekete, Ladislav; Masek, Josef; Hubatka, Frantisek; Turanek, Jaroslav (Analytical chemistry, 2016)
The development of new methods and strategies for the investigation of membrane proteins is limited by poor solubility of these proteins in an aqueous environment and hindered by a number of other problems linked to the instability of the proteins outside lipid bilayers. Therefore, current research focuses on an analysis of membrane proteins incorporated into model lipid membrane, most frequently liposomes. In this work, we introduce a new electrochemical methodology for the analysis of transmembrane proteins reconstituted into a liposomal system. The proposed analytical approach is based on proteoliposomal sample adsorption on the surface of working electrodes followed by analysis of the anodic and cathodic signals of the reconstituted proteins. It works based on the fact that proteins are electroactive species, in contrast to the lipid components of the membranes under the given experimental conditions. Electroanalytical experiments were performed with two transmembrane proteins; the Na(+)/K(+)ATPase that contains transmembrane as well as large extramembraneous segments and the mitochondrial uncoupling protein 1, which is a transmembrane protein essentially lacking extramembraneous segments. Electrochemical analyses of proteoliposomes were compared with analyses of both proteins solubilized with detergents (C12E8 and octyl-PoE) and supported by the following complementary methods: microscopy techniques, protein activity testing, molecular model visualizations, and immunochemical identification of both proteins. The label-free electrochemical platform presented here enables studies of reconstituted transmembrane proteins at the nanomolar level. Our results may contribute to the development of new electrochemical sensors and microarray systems applicable within the field of poorly water-soluble proteins.
Keywords: sodíko-draslíková ATPasa; Uncoupling Protein 1; Liposomes; uncoupling protein 1; Sodium-Potassium-Exchanging ATPase; Humans; lidé; elektrochemické techniky; Electrochemical Techniques; liposomy